THEORETICAL ASPECTS OF THE FORMATION OF ENVIRONMENTAL CULTURE OF YOUNG SCHOOLCHILDREN IN EXTRACURRICULAR ACTIVITIES - Sevinj Valiyeva Tofig (International Journal of Innovative Technologies in Social Science, 2023)
The article emphasizes the characteristic features of the process of formation of environmental culture among young students in extracurricular activities. Elementary school is the most favorable period for environmental education, and the ways of forming a positive and correct attitude towards nature in the majority of children at the elementary school age are analyzed. In extracurricular activities, the tasks of forming the environmental culture of elementary school students are indicated. The main components of the ecological culture formation system are determined. The basic conditions for the successful formation of ecological culture are described. The theoretical aspects of the formation of a protective, careful and responsible attitude towards inanimate and living nature objects in students are analyzed. It is during the elementary school age that the child has an emotional impression of nature, the formation of ideas about the various forms of life on the Earth, and as a result, directions for the formation of fundamental principles of ecological consciousness, thinking, and culture are shown. The main content of the effectiveness of extracurricular activities in the formation of environmental culture of young students is analyzed.